Oscillatory Characteristics of Flow Rate in Cyclone Chambers of High Relative Length - A. N. Orekhov; E. N. Saburov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper describes an experimental investigation pertaining to distribution of oscillatory and averaged tangential and axial velocities of turbulent flow in cyclone chambers of high relative length. It has been shown that as in the chambers of relatively small length (close to unit length) general level of velocity pulsation intensity significantly exceeds the level observed in the chambers of analogous use with non-tightened-up heat carrier.